Penilaian Jejak Karbon (Carbon Footprint) yang Dihasilkan oleh Aktivitas Penduduk di Kawasan Gading Serpong, Tangerang - Zulpikar, Firman; Brennette, Angela (Surya Octagon Interdisciplinary Journal of Science and Technology, 2018)
The development of new residential areas using independent city concept encourages the potential increase of greenhouse gas emissions. It is derived from new infrastructure development and residents activities in this area. The objective of this study was to estimate the amount of greenhouse gas emissions through carbon footprint calculations derived from the resident's activities in Gading Serpong, Tangerang. Carbon footprint values were conducted by questionaire from 200 respondents and from three different types of housing: clusters, sectors and general houses in villages around the area. The emission sources were calculated including transportation, energy use at home, food consumption, and lifestyle. The results showed that lifestyle gave the highest value contribution about 39% of total carbon footprint, followed by transportation and energy use at home around 30% and 27%, respectively. The average value of individual carbon footprint approximately 7.99 tCO2 Eq./year. Moreover, carbon footprint values for cluster-type, sectors-type and general houses in the village were 9,602, 8,453 and 5,009 tCO2 Eq./year respectively. The result also found that the resident's income has a significant contribution to carbon footprint value.This study showed that the carbon footprint value of residents in Gading Serpong area influenced by housing type and individual income level.